The role of time and species identities in spatial patterns of species richness and conservation - Judi E. Hewitt; Simon F. Thrush; Kari E. Ellingsen (Conservation Biology, 2016)
Many conservation actions are justified on the basis of managing biodiversity. Biodiversity, in terms of species richness, is largely the product of rare species. This is problematic because the intensity of sampling needed to characterize communities and patterns of rarity or to justify the use of surrogates has biased sampling in favor of space over time. However, environmental fluctuations interacting with community dynamics lead to temporal variations in where and when species occur, potentially affecting conservation planning by generating uncertainty about results of species distribution modeling (including range determinations), selection of surrogates for biodiversity, and the proportion of biodiversity composed of rare species. To have confidence in the evidence base for conservation actions, one must consider whether temporal replication is necessary to produce broad inferences. Using approximately 20 years of macrofaunal data from tidal flats in 2 harbors, we explored variation in the identity of rare, common, restricted range, and widespread species over time and space. Over time, rare taxa were more likely to increase in abundance or occurrence than to remain rare or disappear and to exhibit temporal patterns in their occurrence. Space–time congruency in ranges (i.e., spatially widespread taxa were also temporally widespread) was observed only where samples were collected across an environmental gradient. Fifteen percent of the taxa in both harbors changed over time from having spatially restricted ranges to having widespread ranges. Our findings suggest that rare species can provide stability against environmental change, because the majority of species were not random transients, but that selection of biodiversity surrogates requires temporal validation. Rarity needs to be considered both spatially and temporally, as species that occur randomly over time are likely to play a different role in ecosystem functioning than those exhibiting temporal structure (e.g., seasonality). Moreover, temporal structure offers the opportunity to place management and conservation activities within windows of maximum opportunity.